Enhanced absorption house connection station for low district heating return line temperatures. (October 2021) - Petersen, Stefan; Albers, Jan
Abstract: Since the first publishing of district heat driven heat pumps at AGFW fair in 2014 in Frankfurt am Main, Germany, introducing a concept how to use additionally the district heat return line as low temperature heat source, the topic gains more and more international scientific and public interest. Hydraulic concepts with and without an additional heat exchanger in the district heat supply line are tested at least in China and Germany. In theory, a reduction of temperature in the district heating return line (DH-rl) can be expected in the range of 25 to 30 K in comparison to standardized DH house connection stations (HCS). However, when the same heat pump is used in cooling mode during summer time, DH-rl temperature reduction in heating mode is limited to a range of 15 to 20 K, due to absorption chiller hydraulics and system design. In the first part of this contribution experimental results are presented which show how the expected reduction of 25 to 30 K has been achieved in practice by an adapted heat pump design. In the second part a new hydraulic design and control concept for the district heat supply flow rate will be presented which enables even higher DH glides also for retrofitted heating systems. Operating a house heating system at 65/45 °C with a conventional HCS may lead to a temperature in DH-rl in the range of 48 – 55 °C. With the first concept of an absorption HCS from 2014 a DH return temperature of 30 – 35 °C is possible, whereas, with the new hydraulic concept the return temperature may decrease down to 20 – 30 °C for layout conditions. In comparison to conventional HCS the enhanced absorption HCS allows to save 15 – 40 % of volume flow rate for the same heating capacity, mainly depending on temperature level of district heat and house heating system. By means, the heat losses in DH networks can be reduced and the transport capacity (i.e. the number of potential households to be served) can by increased. Concept and calculated results for the enhanced absorption HCS are presented.